Thermal performance of traditional and contemporary mosque buildings in the Sultanate of Oman - Al Rasbi, Haitham (2024)
The objectives of enhancing building energy efficiency and ensuring human thermal comfort are often challenging to achieve concurrently. Oman’s climate is hot and dry, and its buildings have high cooling demands. This research aims to investigate the thermal performance of buildings in Oman and improve it without compromising human thermal comfort. Mosque buildings are an interesting case for this research, as daily prayers are conducted intermittently throughout every day. An enhancement in the energy efficiency of mosque buildings would contribute to environmental sustainability through the reduction of energy consumption. This research project aims to investigate two types of mosques: traditional mosque buildings that are 500 years old or older, and contemporary mosque buildings that have been built recently within the last 40 years. There are two primary research methodologies followed in this study: Computer Simulations, and Field Measurements. The computer simulation methodology utilises energy modelling using EDSL TAS computer simulation software. The field measurements methodology is conducted using thermal measurement instruments including temperature and humidity dataloggers. Findings from both the computer simulation and the field measurements were compared for analysis and discussion. The analysis compared between the traditional and contemporary mosque buildings. The objective was to identify solutions for improving building thermal performance and occupants’ thermal comfort. The findings show that traditional buildings, which are naturally ventilated, perform better than contemporary buildings. During the winter, findings from both the field measurements and computer simulations concur that all mosques are within the thermal comfort zone as per the Muscat bioclimatic chart. During the summer, the case studies exceeded the maximum thermal comfort zone temperature despite their high energy consumption. This indicated room for improvement in both the energy efficiency and thermal comfort of the case studies. After a thorough review of the academic literature, field measurements, and computer simulations, a total of fourteen suggested improvements were presented in Chapter 8 (Suggested Improvements Chapter). The initial set of nine improvements were made to enhance the building elements’ conductivity, glazing area, and material composition of walls and roof in the six mosques. The subsequent five improvements were suggested to improve the internal conditions of the buildings and to incorporate passive cooling techniques, such as adjusting the cooling thermostat setpoint, reducing infiltration rate, introducing higher efficiency lighting, introducing a Khalwah (an underground chamber), and increasing vegetation around the buildings. The proposed improvements aim to optimise thermal performance and create more comfortable environments within the mosque buildings. These suggested improvements were carefully combined into three distinct combinations, each of which represented the most effective enhancements tailored to the specific needs of individual mosques targeting three key parameters: Resultant Temperature (RT), Cooling Load (CL), and Predicted Mean Vote (PMV). The first combination was designed to enhance the Resultant Temperature (RT) parameter, leading to a 24% improvement compared to the baseline model. For the second combination, the most effective improvements were combined to address the Cooling Load (CL) parameter, yielding a 58% reduction in cooling load compared to the baseline model. Lastly, the third combination focused on optimising the Predicted Mean Vote (PMV) parameter, resulting in a reduction of up to 15% in annual discomfort hours. These suggested improvements have the potential to offer significant benefits for clients, architects, builders, and stakeholders in the region to provide a pathway to achieve both energy efficiency and thermal comfort in building designs.